Determination of Sustainable Financial Index: BUKU 4 Period 2016 â€“ 2019 - Kusumahadi, Teresia Angelia; Pratikto, Adji; Ruli, Ansgarius Davin (Faculty of Economics Universitas Atma Jaya Yogyakarta, 2021)
Sustainable finance is one of the instruments that can be used to achieve sustainable development goals. Practices of sustainable finance are regulated in the Financial Services Authority Regulation No. 51 / POJK.03 / 2017 (â€œPOJK 51â€), where one of the requirements in its implementation is to publish a Sustainability Report annually. However, before being obliged to release a Sustainability Report, banks, particularly BUKU 4, had published the report. Seeing that the Sustainability Report has been prepared before reporting requirements, these banks are running a sustainable business. To measure the level of sustainability of a bank, we build a Sustainable Financial Index. The Sustainable Financial Index is compiled based on 42 indicators built on sustainable financeâ€™s eight principles. Using Bank Mandiri, BCA, BNI, BRI, and Bank CIMB as the observed bank, the results show that the Sustainable Financial Index for each bank has increased from year to year. The increment indicates that the practice of sustainable finance is running well in BUKU 4. Besides, each bank has different characteristics; thus, the principles that stand out in implementing sustainable finance differ from one bank to another. However, the index has several limitations, so that further index development is required.Keywords:Â BUKU 4, Sustainable Financial Index, POJK 51, Sustainability Report